The microbiome and systemic sclerosis: A review of current evidence. Issue 3 (September 2021) - Tan, Tze Chin; Noviani, Maria; Leung, Ying Ying; Low, Andrea Hsiu Ling
Abstract: Systemic sclerosis (SSc) is characterized by immune dysregulation, vasculopathy, and fibrosis of multiple organs. The gastrointestinal (GI) tract is the most common internal organ manifestation, which contributes to significant morbidity and mortality in patients with SSc. Emerging reports have identified unique microbial taxa alterations in the GI microbiome of patients with SSc as compared to healthy controls (HC). These taxa alterations include differences at the phyla (e.g., Bacteroidetes) and genera (e.g., Bacteroides, Clostridium, Faecalibacterium, and Lactobacillus ) level. In addition, some genera have been associated with more severe GI symptoms (e.g., Prevotella and Akkermansia ). This review summarizes the current evidence on factors influencing the GI microbiome, GI microbiome alterations in SSc as compared to HC, and in SSc subgroups according to disease manifestations. Current exploration in therapeutic interventions that target the GI microbiome is discussed.